2013
DOI: 10.3897/zookeys.269.4619
|View full text |Cite
|
Sign up to set email alerts
|

Key for European species of the Cheilosia proxima group (Diptera, Syrphidae) with a description of a new species

Abstract: A new hoverfly species, Cheilosia barbafacies Vujić & Radenković sp. n. (Diptera, Syrphidae), is described and distinguished from the closely related species Cheilosia pascuorum Becker, 1894, based on material collected from the mountains of the Balkan Peninsula. Diagnostic characteristics and an identification key for the members of the proxima group of Cheilosia s. str., including the new taxon, are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Thompson et al (2010) reported 439 species of Cheilosia known worldwide, and Vujić et al (2013), Ricarte et al (2014), Barkalov and Ståhls (2015), Barkalov and Ichige (2016) added altogether six species, thus the present total number is 445. Barkalov (2002) classified the Cheilosia species into 13 subgenera, of which nine were new ( Cheilosia Meigen, 1822; Endoiasimyia Bigot, 1882 (= Sonanomyia Shiraki, 1930); Taeniochilosia Oldenberg, 1916 (= Nigrocheilosia Shatalkin, 1975); Hiatomyia Shannon, 1922; Neocheilosia Barkalov, 1983; Eucartosyrphus Barkalov, 2002; Floccocheila Barkalov, 2002; Pollinocheila Barkalov, 2002; Montanocheila Barkalov, 2002; Nephocheila Barkalov, 2002; Conicheila Barkalov, 2002; Convocheila Barkalov, 2002 and Rubrocheila Barkalov, 2002.…”
Section: Introductionmentioning
confidence: 82%
“…Thompson et al (2010) reported 439 species of Cheilosia known worldwide, and Vujić et al (2013), Ricarte et al (2014), Barkalov and Ståhls (2015), Barkalov and Ichige (2016) added altogether six species, thus the present total number is 445. Barkalov (2002) classified the Cheilosia species into 13 subgenera, of which nine were new ( Cheilosia Meigen, 1822; Endoiasimyia Bigot, 1882 (= Sonanomyia Shiraki, 1930); Taeniochilosia Oldenberg, 1916 (= Nigrocheilosia Shatalkin, 1975); Hiatomyia Shannon, 1922; Neocheilosia Barkalov, 1983; Eucartosyrphus Barkalov, 2002; Floccocheila Barkalov, 2002; Pollinocheila Barkalov, 2002; Montanocheila Barkalov, 2002; Nephocheila Barkalov, 2002; Conicheila Barkalov, 2002; Convocheila Barkalov, 2002 and Rubrocheila Barkalov, 2002.…”
Section: Introductionmentioning
confidence: 82%
“…Numerous recent studies concerning the Cheilosia fauna of the Palaearctic region have continued to add new taxa to the genus (e.g. Claussen, 2000;Barkalov & Cheng, 2004;Claussen & Ståhls, 2007;Vujić et al, 2013;Barkalov & Ståhls, 2015). Rhingia, Pelecocera, and Ferdinandea are genera with wide distributions and moderately high numbers of species (Table 1), but with few recent descriptions of taxa new to science (e.g.…”
Section: Rhingiini: High Taxonomic Diversitymentioning
confidence: 99%
“…Molecular phylogenetic studies of Syrphidae taxa have frequently employed the mitochondrial cytochrome c oxidase subunit I (hereafter COI), nuclear 28S and 18S ribosomal RNA genes, that proved to be informative for both generic and species levels (e.g. Mengual, Ståhls & Rojo, 2008, 2015bReemer & Ståhls, 2013;Vujić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Brown (1991) identified 12 "desirable qualities" for insect indicator taxa in order to be efficient: taxonomically and ecologically highly diversified, species have high ecological fidelity, relatively sedentary, species narrowly endemic, or if widespread, well differentiated, taxonomically well known, easy to identify, well studied, abundant, non-furtive, easy to find in the field, damped fluctuations (always present), easy to obtain large random samples of species and variation; functionally important in ecosystem, response to disturbance predictable, rapid, sensitive, analyzable and linear, and associates closely with and indicates other species and specific resources. In addition to a majority of these criteria hoverflies met, hoverflies of Serbia are particularly well studied (Glumac, 1955(Glumac, , 1959Vujić and Glumac, 1994;Vujić, 1996;Vujić and Šimić, 1994;Šimić et al, 2009;Vujić, 1984, 1996;Radenković, 2008;Nedeljković et al, 2009;Vujić et al, 2013;Vujić et al, 2016). This is of the utmost importance when applying StN analysis.…”
Section: Introductionmentioning
confidence: 99%